On the solvability of physically nonlinear problems of Thermoelasticity - Komarov, G. N.; Oshkhunov, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We study the problem of existence and uniqueness of generalized solutions of nonlinear vector boundary-value problems arising in the physically nonlinear theory of thermoelasticity. We prove the convergence of iteration processes in the space W 1 2.